2018
DOI: 10.3904/kjim.2016.282
|View full text |Cite
|
Sign up to set email alerts
|

Use of hypnotics and the risk of or mortality from heart disease: a meta-analysis of observational studies

Abstract: Background/AimsSome observational epidemiologic studies have reported conflicting results on the relationship between hypnotics use and the risk of developing and/or dying from heart disease. We investigated these associations using a meta-analysis of available literatures.MethodsWe searched the databases PubMed and EMBASE, along with the bibliographies of relevant articles to find additional publications in February 2016.ResultsOf 495 articles satisfying our initial criteria, two case-control studies and six … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 35 publications
1
14
0
Order By: Relevance
“…In comparing the PSQI scores between the studied individuals, the present study found a significant relationship between the use of sleep medication and the severity of CVR (p value = 0.023) compared to the results of the study of Kim et al 2018 who found that the risk of mortality from CVD was significantly decreased with the use of hypnotics (29) . The reason for the difference in the results could be that most participants in our study did not receive sleep medications during the last month.…”
Section: Discussionsupporting
confidence: 50%
“…In comparing the PSQI scores between the studied individuals, the present study found a significant relationship between the use of sleep medication and the severity of CVR (p value = 0.023) compared to the results of the study of Kim et al 2018 who found that the risk of mortality from CVD was significantly decreased with the use of hypnotics (29) . The reason for the difference in the results could be that most participants in our study did not receive sleep medications during the last month.…”
Section: Discussionsupporting
confidence: 50%
“…The use of sedative-hypnotics may be due to insomnia as a symptom of the depression and anxiety found commonly in patients with circulatory conditions [ 34 , 35 ]. However, studies on the risk of mortality from heart disease in sedative-hypnotic uses are inconsistent [ 36 , 37 ]. Some studies even indicated that hypnotic use might be related to lower mortality [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…10 There is also concern that long-term use of z-drugs may increase the risk of cardiovascular events, cancer, and all-cause mortality, but the data thus far have only come from observational trials and findings have been inconsistent. [12][13][14] Antidepressants are a strong treatment alternative especially in patients reporting comorbid mood disorders. Cognitive behavioral therapy as noted above is a more effective long-term solution for insomnia than simply using an antidepressant.…”
Section: Pharmacologic Treatmentmentioning
confidence: 99%
“…10 There is also concern that long-term use of z-drugs may increase the risk of cardiovascular events, cancer, and all-cause mortality, but the data thus far have only come from observational trials and findings have been inconsistent. 1214…”
Section: Literature Reviewmentioning
confidence: 99%